The (ir)reversibility of English binomials: corpus, constraints, developments - Mollin, Sandra (Studies in corpus linguistics, 2014)
This book focuses on binomials (word pairs such as heart and soul, rich and poor, or if and when), and in particular on the degree of reversibility that English binomials demonstrate. Detailed and innovative corpus linguistic analyses investigate the correlates of the degree of reversibility, linguistic constraints that influence the ordering and reversibility of binomials and the diachronic development of reversibility. In addition, judgment data are analyzed for their convergence and divergence with corpus data regarding degrees of reversibility. The book thus establishes reversibility as a complex characteristic of the binomial construction, at the same time throwing light on general questions in phraseology, lexicalization, language structure and language processing.